The Correlation Between Tumor Necrosis Factors-Alpha (TNF-? ) and Resistin in Obese Iraqi Women - Zinah Abbass Ali1 , Khawla A. Shemran2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Obesity is a medical condition in which excess body fat has accumulated to an extent that it may have anegative effect on health. The current study aimed to study the correlation between resistin and TumorNecrosis Factors-alpha (TNF-?) in Obese Iraqi women. The group of patients contain twenty five womenwith Obesity and apparently thirty healthy women were present as a control group. Estimation of seraresistin and Tumor Necrosis Factors-alpha (TNF-? ) were done by using “enzyme-linked immunosorbentassay” (ELISA). Sera levels of resistin was increase significantly in women with obesity group comparedwith control group (p<0.01). Also the results show positive correlation between Tumor Necrosis Factorsalpha (TNF-? and resistin. In women with obesity, depending on present findings, resistin is implicated inpathogenesis of obesity related with Tumor Necrosis Factors-alpha (TNF-? ) .